A Review of the Recent Developments in Synthetic Anti-Breast Cancer Agents - Singh, Parvesh; Ngcoya, Nomandla; Kumar, Vipan (Anti-Cancer Agents in Medicinal Chemistry, 2016)
The perceptible decrease in the incidence of breast cancer in recent years has not influenced its societal and economic impact and it remains as the most commonly diagnosed malignancies among females. Recent reports of clinical trials in preventive settings suggested chemoprevention as an appealing strategy zeroing heavily on endocrine intervention using selective estrogen receptor modulators (SERMs) and aromatase inhibitors (AIs). Unfortunately, these drugs are only effective in prevention of endocrine responsive lesions with essentially no effect in reducing the risk of estrogen-negative breast cancer. Further, the existing drugs for breast cancer treatment are invariably associated with several drawbacks such as poor oral bioavailability, non-selectivity and poor pharmacodynamics properties, limiting their clinical utility. Thus, the identification of new molecular targets and the development of agents with better pharmacological profiles will streamline the development of rational, effective and safe anticancer drugs with minimal side-effects. Over the past few years, different research groups have been actively involved in the design and synthesis of novel anti-breast cancer agents. In this review article, the recent developments (2013 onwards) made in the direction of synthesis of new scaffolds with promising anti-breast cancer activity, are briefly described. Hopefully, the data compiled in this article will update scientific community with recent endeavors in this field, and will certainly be encouraging for further research in this direction.
Keywords: Breast cancer